Late Gadolinium Enhancement Cardiac Magnetic Resonance Tissue Characterization for Cancer‐Associated Cardiac Masses: Metabolic and Prognostic Manifestations in Relation to Whole‐Body Positron Emission Tomography - Angel T. Chan; Josef Fox; Rocio Perez Johnston; Jiwon Kim; Lillian R. Brouwer; John Grizzard; Raymond J. Kim; Mathew Matasar; Jinru Shia; Chaya S. Moskowitz; Richard Steingart; Jonathan W. Weinsaft (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Cardiac magnetic resonance (CMR) differentiates neoplasm from thrombus via contrast enhancement; positron emission tomography (PET) assesses metabolism. The relationship between CMR contrast enhancement and metabolism on PET is unknown. Methods and Results The population included 121 cancer patients undergoing CMR and 18F‐fluorodeoxyglucose (18F‐FDG)–PET, including 66 with cardiac masses and cancer‐matched controls. Cardiac mass etiology (neoplasm, thrombus) on CMR was defined by late gadolinium enhancement; PET was read blinded to CMR for diagnostic performance, then colocalized to measure FDG avidity. Of CMR‐evidenced thrombi (all nonenhancing), none were detected by PET. For neoplasm, PET yielded reasonable sensitivity (70–83%) and specificity (75–88%). Lesions undetected by PET were more likely to be highly mobile (P=0.001) despite similar size (P=0.33). Among nonmobile neoplasms, PET sensitivity varied in relation to extent of CMR‐evidenced avascularity; detection of diffusely enhancing or mixed lesions was higher versus predominantly avascular neoplasms (87% versus 63%). Colocalized analyses demonstrated 2‐ to 4‐fold higher FDG uptake in neoplasm versus thrombus (P<0.001); FDG uptake decreased stepwise when neoplasms were partitioned based on extent of avascularity on late gadolinium enhancement CMR (P≤0.001). Among patients with neoplasm, signal‐to‐noise ratio on late gadolinium enhancement CMR moderately correlated with standardized uptake values on PET (r=0.42–0.49, P<0.05). Mortality was higher among patients with CMR‐evidenced neoplasm versus controls (hazard ratio: 1.99 [95% CI, 1.1–3.6]; P=0.03) despite nonsignificant differences when partitioned via FDG avidity (hazard ratio: 1.56 [95% CI, 0.85–2.74]; P=0.16). Among FDG‐positive neoplasms detected concordantly with CMR, mortality risk versus cancer‐matched controls was equivalently increased (hazard ratio: 2.12 [95% CI, 1.01–4.44]; P=0.047). Conclusions CMR contrast enhancement provides a criterion for neoplasm that parallels FDG‐evidenced metabolic activity and stratifies prognosis. Extent of tissue avascularity on late gadolinium enhancement CMR affects cardiac mass identification by FDG‐PET.